Relationship of positive valence WOM and customer loyalty in social media: trust, value co-creation, and brand image as mediators - Indradewa, Rhian; Riyanto, Aris (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
In the midst of increasingly tight business competition, with numerous imitations of business ideas and solutions, competitive advantage alone is not sufficient to maintain customer loyalty. Considering the importance of maintaining customer loyalty, this study aims to analyze the relationship between positive valence WOM (PVWOM) and customer loyalty, with mediating factors such as trust, value co-creation, and brand image. This research is expected to contribute to theoretical understanding of the variables under study and provide managerial implications to organizations in various industry sectors. It is also hoped to strengthen our understanding of PVWOM in social media, assist marketers in gaining insights into the factors influencing the relationship between PVWOM and customers on social media, and aid them in designing digital marketing strategies. This research involves 4 schools in Kabupaten Bekasi with a total of 210 respondents over three months. Data were analyzed using Structural Equation Model (SEM) AMOS. The results show a positive relationship between PVWOM and customer loyalty, with trust, value co-creation, and brand image partially mediating this relationship. Additionally, the research findings support a serial mediation model where PVWOM influences loyalty through trust and value co-creation sequentially. Managerial implications applicable to the education sector include the notion that a good level of positive valence WOM will enhance proactive attitudes in teaching and learning activities, as well as foster collaborative knowledge creation. Current conditions urge educational institutions to innovate information and communication technology in every teaching and learning activity. Positive valence WOM can be enhanced through social networks interacting to obtain innovative ideas and insights from their customers. If educational institution customers can actively participate in decision-making, then positive valence WOM can be leveraged to impact management within educational institutions.